PENYELESAIAN PERMASALAHAN BARAK DAN SHELTER PENYINTAS TSUNAMI 26 DES EMBER 2004 DI NAGGROE ACEH DARUSSALAM - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
After earthquake and tsunami devastated, many temporary shelters (tent, barracks, and shelter) were constructed in NanggroeAceh Darussalam. Housing becamethemost important issuesin post disastermanagement. The main issuewas to count how manyfamilies would becomebeneficiariesof the reconstructed housesdue to some people had died, missing, taken refuge elsewhere, or moving to other towns. If the counting was not accurate, tsunami victims' who had rights might not receivehousesand/or might receivemore than one.Many of deviations occur in the distribution processof housing and settlement assistancecomesfrom temporary shelter. Learningfrom Aceh that lack of organization in the early stageof emergency responsehad causedIDPs locations to initially miss out on the data collection process.The various survey methodswere difficult to conduct. To overcomethe problem, a unique strategy in counting the beneficiaries was formulated. Completing barracks'problems may be the last indicator of thefulfillment of housing assistance.